Impact of Histopathological Examination of Appendix on Clinical Management of Patients - GK Parvathidevi,; Sriharsha HV,; Srusti HV,; Keertana Raghavendra, (The Bioscan, 2025)
INTRODUCTION Acute appendicitis is one of the common conditions requiring emergency surgery. In routine practice appendix is sent for histopathological examination only when operative findings are inconclusive. In view of this trend in clinical practice this study was carried out to assess the value of routine histopathological examination of surgically resected appendices. OBJECTIVES: 1. To study spectrum of histopathological lesions. 2. To analyse the proportion of various lesions, age & sex distribution 3. To find out proportion of unusual findings in appendicectomy specimens METHODS: A retrospective study was done including appendicectomy specimens received at histopathology section of Dept of pathology at our institute from February 2023 till July 2024. RESULTS: A total of 210 cases were reviewed. Out of those, clinically suspected appendicitis was found in 193(91.9%) cases including spectrum of appendicitis [acute, recurrent, chronic, suppurative, acute on chronic, acute with periappendicitis, gangrenous acute with perforation]. Unusual findings were found in 11(5.23%) cases [tuberculosis, amoebiasis, fecolith , xanthogranulomatous inflammation, retention mucocele and neoplastic lesions including carcinoid, Low grade appendiceal mucinous neoplasm, adenocarcinoma]. CONCLUSION: Though majority of cases had the usual features, 11 of these 210 spectrum(5.23%) had an impact on patient management & outcome. They were not suspected on macroscopic examination at the time of surgery and would have been missed had the specimens not been examined microscopically. Intra-operative diagnosis of surgeon is therefore unreliable in detecting abnormalities of appendix. The study supports the sending of all appendicectomy specimens for routine histopathological examination.